2011
DOI: 10.1227/neu.0b013e31821954ed
|View full text |Cite
|
Sign up to set email alerts
|

Learning Retention of Thoracic Pedicle Screw Placement Using a High-Resolution Augmented Reality Simulator With Haptic Feedback

Abstract: Background We evaluated the use of a part-task simulator with 3D and haptic feedback as a training tool for a common neurosurgical procedure – placement of thoracic pedicle screws. Objective To evaluate the learning retention of thoracic pedicle screw placement on a high-performance augmented reality and haptic technology workstation. Methods Fifty-one fellows and residents performed thoracic pedicle screw placement on the simulator. The virtual screws were drilled into a virtual patient’s thoracic spine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 23 publications
1
71
0
1
Order By: Relevance
“…Although computer-based simulators have been developed to facilitate the acquisition of screw placement skills, it remains unclear whether this on-screen practice can translate into increased accuracy and comfort in the operating room. 5,7,13 The challenges that trainees face are, in part, related to limited clinical hands-on exposure and the need to acquire an understanding of complex 3D spinal anatomy. For non-video-assisted procedures such as spinal surgery, the incorporation of cadaveric training into the resident educational process is likely to remain a critical component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although computer-based simulators have been developed to facilitate the acquisition of screw placement skills, it remains unclear whether this on-screen practice can translate into increased accuracy and comfort in the operating room. 5,7,13 The challenges that trainees face are, in part, related to limited clinical hands-on exposure and the need to acquire an understanding of complex 3D spinal anatomy. For non-video-assisted procedures such as spinal surgery, the incorporation of cadaveric training into the resident educational process is likely to remain a critical component.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 A number of recent studies have attempted to compare the benefits of various laboratorybased techniques, although most do not demonstrate significant benefit. 7,9,14 To date, a definitive, evidence-based, laboratory training module has not been delineated.…”
mentioning
confidence: 99%
“…The most commonly used simulator was ImmersiveTouch, an augmented virtual reality system that has been shown to improve performance when used for training to simulate ventriculostomy, 5,6,27,28,57 thoracic pedicle screw placement, 29 and percutaneous spinal needle placement 30 across different grades of trainees. Ventriculostomy was the commonest simulated procedure identified from this systematic review, having been reported in 6 articles.…”
Section: Data Synthesismentioning
confidence: 99%
“…Examples in neurosurgery include simulators for ventriculostomy [27,30,38], spine needle biopsy [28], pedicle screw placement [26,31], diagnostic cerebral angiography [53], and aneurysm clipping. However, there may be limitations in the ability to transfer these "virtual skills" to physical reality [20,39].…”
mentioning
confidence: 99%